2012
DOI: 10.4238/2012.october.17.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between heifer subsequent rebreeding and age at first calving and growth traits in Nellore cattle by Bayesian inference

Abstract: ABSTRACT. We estimated heritability for subsequent rebreeding (SR) of heifers and genetic correlations between this trait and weaning weight (WW), weight gain from weaning to yearling (WG), age at first calving (AFC), and mature cow weight (MW), in order to evaluate whether SR could be included as selection criterion in Nellore cattle. The SR of heifers was defined by attributing a value of 1 (success) or 0 (failure) to heifers that calved or not, respectively, given that they had calved once before. Records f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Laureano et al (2011) estimated a lower heritability (0.23) by the restricted maximum likelihood method. Using Bayesian analysis, Van Melis et al (2010) and Boligon et al (2012) reported heritabilities of 0.25 and 0.30, respectively, for postweaning weight gain in the Nellore cattle. The posterior estimate of heritability obtained in the present study agrees with those reported by other authors for Nellore populations, suggesting that direct selection for this trait should result in genetic progress in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Laureano et al (2011) estimated a lower heritability (0.23) by the restricted maximum likelihood method. Using Bayesian analysis, Van Melis et al (2010) and Boligon et al (2012) reported heritabilities of 0.25 and 0.30, respectively, for postweaning weight gain in the Nellore cattle. The posterior estimate of heritability obtained in the present study agrees with those reported by other authors for Nellore populations, suggesting that direct selection for this trait should result in genetic progress in the population.…”
Section: Discussionmentioning
confidence: 99%
“…effect and without maternal permanent environment effect) and with model 3 (without maternal genetic effect and with maternal permanent environment effect), using df = 1. For AFC, the maternal random genetic effects and the permanent environmental effects were not tested, as seen in other studies (Buzanskas et al, 2010;Laureano et al, 2011;Boligon et al, 2012), because the influence of these components is observed mainly until weaning (Boligon et al, 2010). The inclusion of the maternal random genetic effect and the permanent environmental effect in the model was also not evaluated for the remaining traits, because the structure of the data set and the pedigree records was not sufficient to estimate them.…”
Section: Likelihood Ratio Testmentioning
confidence: 99%
“…Otros investigadores (Lôbo 1998, Yilmaz et al 2004, Roughsedge et al 2005, Azevêdo et al 2006b, Boligon et al 2012 han reportado menores estimadores con valores que van (2005) reportaron estimadores de heredabilidad cercanos a cero, sugiriendo que la varianza genética aditiva para edad a primer parto es escasa. Bajos estimadores de heredabilidad para edad a primer parto pueden deberse a la corta duración de los empadres de las vaquillas, ya que con empadres más largos se pueden concebir más hembras, lo que puede contribuir a la identificación de diferencias genéticas entre animales (Forni y Albuquerque 2005).…”
Section: Edad Al Primer Partounclassified
“…En consecuencia, el estimador de repetibilidad fue similar al estimador de heredabilidad. Este último sugiere que la selección sería efectiva; además, es similar a los estimadores reportados para vacas Angus (0,45; Northcutt y Wilson 1993) y Nelore (0,45; Boligon et al 2012). Con vacas Angus, Hereford y F1 Angus x Hereford, Arango et al (2002) obtuvieron una heredabilidad para peso maduro de 0,49, valor que es igual al estimado en el presente estudio.…”
Section: Peso De La Vacaunclassified